Digital Technologies and Generational Identity ICT Usage Across the Life Course - ICT Usage Across the Life Course (ICT Usage Across the Life Course, 2017)
The short lifetime of digital technologies means that generational identities are difficult to establish around any particular technologies let alone around more far-reaching socio-technological ‘revolutions’. Examining the consumption and use of digital technologies throughout the stages of human development, this book provides a valuable overview of ICT usage and generational differences. It focuses on the fields of home, family and consumption as key arenas where these processes are being enacted, sometimes strengthening old distinctions, sometimes creating new ones, always embodying an inherent restlessness that affects all aspects and all stages of life.